Entre a teoria, a prática e a tecnologia: articulações entre o saber teórico e o saber prático no contexto da formação contábil articulações entre o saber teórico e o saber prático no contexto da formação contábil - Moreira, Josicleide de Amorim Pereira (2013)
Taking into account the changes in this globalized world, whose consequences echo in the accounting setting, in which their effects are manifested in reflections, theories and social, tax or normative practices, it is realized that the accountant needs a theoretical and practical formation that fosters a professional profile which makes feasible better organizational results and social development. Hence, accounting formation should encompass the necessary competences so that the course s graduate student can be placed in the labor market so as to respond to its demands as well as to the settings of the global economic policies, consciously and critically, ensuring thus the citizenship exercise by envisaging better life conditions and information democratization. Due to this fact, this research aimed at analyzing the existent relationship between the theoretical knowledge and the practice knowledge in the Accounting formation from the pedagogical-political fundamentals of Higher Education in the state of Paraíba. Consequently, Jürgem Habermas´ contributions to the Theory of Communicative Action were used with the intention to understand the relation established between the theoretical discourse and the practical one, having as starting point the definitions of instrumental reason and communicative reason . For the development of this research of empirical classification and quanti-qualitative approach, the exploratory typology was adopted having bibliographical and documental research as procedures. As to data collection, a questionnaire with closed questions was answered by students/trainees from the following public institutions: UFPB Campus I, UFPB Campus IV, UFCG Campus Sousa, UEPB Campus I and UEPB Campus VI. The results obtained from the content analysis of the Pedagogical Projects of the Courses (PPCs) denote the fulfillment of the National Curricular Guidelines (DCNs) by the researched Higher Education Institutions. The analysis of syllabuses of the Laboratory of Practices demonstrates that the activities inherent to the exercise of accounting profession were not fully covered. Time dedicated to the total course load is reduced thus highlighting that there is concern with reflection and understanding originated from the objectives of the accounting technique, and with the means on attaining the specific goals, providing instrumental rationality. Questionnaire results reveal that the courses have a highly theoretical design. Practices are not carried out in full time and their focus is on the modus operandi . The training students feel fairly qualified for their entry in the labor market and they are not fully prepared to perform all the activities that are fulfilled by means of technological systems. The duality, that the obtained data make reference to the hypothesis, corroborates the dichotomy itself of the accounting formation that is related to the imperatives of instrumental rationality as well as to the communicative one. It can be concluded, however not acceptable, that in the accounting formation, the practice is dissociated from the theory and vice versa.